Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Which values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] make the equation true?

[tex]\[ \frac{(2xy)^4}{4xy} = 4x^a y^b \][/tex]

A. [tex]\( a=0, b=0 \)[/tex]

B. [tex]\( a=3, b=3 \)[/tex]

C. [tex]\( a=4, b=4 \)[/tex]

D. [tex]\( a=5, b=5 \)[/tex]


Sagot :

To determine which values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] satisfy the equation
[tex]\[ \frac{(2xy)^4}{4xy} = 4x^a y^b, \][/tex]
we first simplify the left-hand side of the equation.

1. Simplify the expression [tex]\((2xy)^4\)[/tex]:
[tex]\[ (2xy)^4 = (2xy)(2xy)(2xy)(2xy) = 2^4 x^4 y^4 = 16x^4 y^4. \][/tex]

2. Now, substitute this back into the fractional term on the left-hand side:
[tex]\[ \frac{(2xy)^4}{4xy} = \frac{16x^4 y^4}{4xy}. \][/tex]

3. Simplify the fraction by dividing the numerator and the denominator by [tex]\( 4xy \)[/tex]:
[tex]\[ \frac{16x^4 y^4}{4xy} = \frac{16x^4 y^4}{4xy} = 4 \cdot \frac{x^4 y^4}{xy} = 4 \cdot x^{4-1} y^{4-1} = 4 x^3 y^3. \][/tex]

So, the left-hand side simplifies to:
[tex]\[ 4 x^3 y^3. \][/tex]

Next, we compare the simplified left-hand side to the right-hand side of the original equation to find the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex].

Given:
[tex]\[ 4 x^3 y^3 = 4 x^a y^b. \][/tex]

For the equation to hold for all [tex]\( x \)[/tex] and [tex]\( y \)[/tex], the exponents on both sides must be equal:
[tex]\[ a = 3 \quad \text{and} \quad b = 3. \][/tex]

Therefore, the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] that satisfy the equation are:
[tex]\[ \boxed{a = 3, b = 3}. \][/tex]